"Reconstructing a Sense of Self": Trauma and Coping Among Returned Women Survivors of Human Trafficking in Vietnam. (March 2017) - Le, PhuongThao D.
Survivors of human trafficking who return to their community of origin must cope with the trauma they experienced as victims as well as the conditions that contributed to their trafficking vulnerabilities. In this article, I examine the psychosocial adjustment process among women survivors of trafficking who returned to Vietnam. Supplemented by participation observation, thematic analysis of in-depth interviews with survivors revealed that throughout the trafficking process, the women experienced multiple abuses and changes in relationships and environments. The women coped by navigating a process of "reconstructing a sense of self, " seeking congruence between their self-understandings and the changing contextual factors while exhibiting three main coping strategies: regulating emotional expression and thought, creating opportunities within constraints, and relating to cultural schemas. The findings underscore the importance of considering contextual factors such as cultural norms and societal values in efforts to assist trafficked survivors reintegrate into their communities.